otal antioxidant status in plasma of breast cancer women in relation to ERβ expression - Zowczak-Drabarczyk, Miłosława Maria; Murawa, Dawid; Kaczmarek, Leszek; Połom, Karol; Litwiniuk, Maria (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study : The aim of this pilot study was to evaluate the plasma total antioxidant capacity (TAS) in breast cancer patients in relation to ERβ expression. Material and methods: The study group consisted of newly diagnosed consecutive female breast cancer patients (n = 41) and controls (n = 28) randomly selected from women with benign breast disease. TAS was determined with the ABTS reagent. Immunostaining for ERβ was performed using polyclonal antibodies. ER, PgR and HER-2 were measured routinely (immunostaining for ER and PgR with monoclonal antibodies and EnVision detection system; immunohistochemical method/FISH for HER-2 expression). Results: The plasma TAS was significantly decreased in the breast cancer patients in comparison to the controls independently of hormonal and lymph node status. The TAS level was not significantly different between breast cancer subgroups either in relation to the ERβ expression (ERβ+ vs. ERβ–) or considering the steroid receptor status (ER+, ERβ+, Pg+ vs. ER+, ERβ–, Pg+) even in the selected lymph node negative subgroup. Similarly, HER-2 expression did not significantly affect the TAS concentration. A tendency towards higher TAS level in all ERβ negative breast cancer subgroups was observed. Conclusions: The results might confirm enhanced consumption of plasma antioxidants in breast cancer patients. The determination of ERβisoforms along with parameters of redox status might enable better understanding of their mutual influence